2015
DOI: 10.2166/9781780407227
|View full text |Cite
|
Sign up to set email alerts
|

Costing Improved Water Supply Systems for Low-income Communities: A Practical Manual

Abstract: The aim of this paper is to present a practical manual prepared for the Department Public Health and Environment now Department for the Protection of the Human Environment of the World Health Organization (WHO) dealing with how to identify, collect, estimate and compare costs of the available technical options to provide access to safe drinking water in low-income communities. To cost an improved water supply technology, likely to secure access to safe drinking-water as defined by the WHO-UNICEF Joint Monitori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 1 publication
1
5
0
Order By: Relevance
“…The main energy source for extracting water in these areas is human physical strength, through hand pumps or with buckets in wells [3]. Such collection techniques are time consuming [4], very physically demanding [5] and prevent from reaching deep aquifers [6].…”
Section: Introductionmentioning
confidence: 99%
“…The main energy source for extracting water in these areas is human physical strength, through hand pumps or with buckets in wells [3]. Such collection techniques are time consuming [4], very physically demanding [5] and prevent from reaching deep aquifers [6].…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we present a practical manual 1 on Costing Improved Water Supply Systems for Low-income Communities prepared for the Department Public Health and Environment of the World Health Organization (WHO), on how to identify, collect, estimate and compare costs of the available technical options to provide access to safe drinking water in low-income communities, namely rural and slum communities. This guidance document intends to contribute in a meaningful way to achieve one of the main targets of the Millennium Development Goals (MDG), namely to halve, by 2015, the proportion of people without sustainable access to safe drinking water and basic sanitation.…”
Section: Introductionmentioning
confidence: 99%
“…In the key informant interviews with the village leaders, it was reported that amount of money to be given to each village government was reported not to be enough to complete even one development project. For instance the amount of money required to complete a water project for the people of more than 1500 households was not less than 200 million (Carlevaro and Gonzalez, 2008). This amount of money is higher by 86 -88% than the amount of money expected to be given to the households and village government put together.…”
Section: Potential Carbon Credit At Village Government Levelmentioning
confidence: 96%